2010
DOI: 10.3177/jnsv.56.271
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cytokeratin 18 M30 Antigen Level and Its Correlation with Nutritional Parameters in Middle-Aged Japanese Males with Nonalcoholic Fatty Liver Disease (NAFLD)

Abstract: Summary Cytokeratin (CK) 18 M30 antigen has been proposed as a diagnostic marker of nonalcoholic fatty liver disease (NAFLD). We studied serum CK18 M30 antigen level and examined the correlations among CK18 and biological data, dietary intake, and plasma fatty acid composition in middle-aged Japanese males with (NAFLD; n ϭ 42) and without NAFLD (control; n ϭ 35). NAFLD was diagnosed if subjects showed fatty liver on abdominal ultrasonography and their alcohol consumption was Ͻ 20 g/d. They were also confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…M30 stains for keratin 18 that has been cleaved by caspase 3, hence identifying apoptotic cells (19). Recent studies have demonstrated that M30 can predict steatosis and hepatocytic injury (21)(22)(23)(24). Our results suggest that a higher concentration of OA will increase the severity of NAFLD.…”
Section: Discussionmentioning
confidence: 65%
“…M30 stains for keratin 18 that has been cleaved by caspase 3, hence identifying apoptotic cells (19). Recent studies have demonstrated that M30 can predict steatosis and hepatocytic injury (21)(22)(23)(24). Our results suggest that a higher concentration of OA will increase the severity of NAFLD.…”
Section: Discussionmentioning
confidence: 65%
“…This was validated by the same group and in a cohort of patients who underwent bariatric surgery, an M30-cutoff value of 275 U/L was established to discriminate simple steatosis from NASH [7, 17]. We and others were able to show that M30 correlates with fatty acid transporter expression in liver tissue and specific fatty acids in the serum [18, 19]. In a cohort of patients with polycystic ovarial syndrome, we could identify a high rate of patients with NASH utilizing this assay [20].…”
Section: Discussion and Reviewmentioning
confidence: 98%
“…It has been demonstrated that SFAs are potentially hepatotoxic through induction of lipoapoptosis (37). So, weight loss can prevent hepatocellular apoptosis in NAFLD through improving fatty acids metabolism (38). …”
Section: Discussionmentioning
confidence: 99%